Towards Right Answer for the Right Reasons in Global Land Carbon Sink Estimates - Helin Zhang; Youngryel Ryu; Sungchan Jeong (Global Change Biology, 2026)
Quantifying the global land carbon sink is essential for understanding carbon‐climate feedbacks and developing effective mitigation strategies. Despite decades of research using eddy covariance, remote sensing, and atmospheric observations, carbon sink estimates remain highly uncertain across different approaches. The key challenge is to obtain the right global land carbon sink estimates for the right reasons. In this review, we first provide an overview of current methodologies for estimating terrestrial carbon sinks, including FLUXNET observations, top‐down atmospheric inversions, and bottom‐up approaches. We then leverage insights learned from FLUXNET to evaluate the observed range of annual net ecosystem exchange (NEE), gross primary production (GPP)–ecosystem respiration (R eco ), and GPP–evapotranspiration (ET) relationships, and assess whether current models capture these observational constraints. Because FLUXNET is widely used as a benchmark for evaluation and as training data for model calibration, we also identify opportunities to strengthen the utility of FLUXNET for global land carbon sink inference.